Diverse Impacts of HIV Latency-Reversing Agents on CD8+ T-Cell Function: Implications for HIV Cure - Clutton, Genevieve Tyndale; Jones, R. Brad (Frontiers in Immunology, 2018)
Antiretroviral therapy (ART) regimens durably suppress HIV replication, but do not cure infection. This is partially attributable to the persistence of long-lived pools of resting CD4+ T-cells harboring latent replication-competent virus. Substantial clinical and pre-clinical research is currently being directed at purging this viral reservoir by combining pharmacological latency reversal with immune effectors, such as HIV-specific CD8+ T-cells, capable of eliminating reactivated targets – the so called ‘shock-and-kill’ approach. However, several studies indicate the latency reversing agents may affect CD8+ T-cell function. The current review aims to frame recent advances, and ongoing challenges, in implementing ‘shock-and-kill’ strategies from the perspective of effectively harnessing CD8+ T-cells. We review and contextualize findings indicating that latency reversing agents often have unintended impacts on CD8+ T-cell function, both detrimental and beneficial. We identify and attempt to bridge the gap between viral reactivation, as measured by the detection of RNA or protein, and bona fide presentation of viral antigens to CD8+ T-cells. Finally, we highlight factors on the effector (CD8+) and target (CD4+) cell sides that contribute to whether or not infected cell recognition results in killing/elimination. These perspectives may contribute to an integrated view of ‘shock-and-kill’, with implications for therapeutic development.